Tropical Western Pacific Hydrology During the Last 6, 000 Years Based on Wildfire Charcoal Records From Borneo. Issue 18 (12th September 2021) - Yamamoto, Masanobu; Kikuchi, Takafumi; Sakurai, Hiromichi; Hayashi, Ryoma; Seki, Osamu; Omori, Takayuki; Sulaiman, Abdullah; Shaari, Hasrizal; Abdullah, Mohd Zulhilmy; Melling, Lulie
Abstract: The forcing of multicentennial climate variability in the Western Pacific Warm Pool (WPWP) region is not fully understood. Here, we generated 6‐kyr‐long continuous charcoal records from five peatlands in Borneo. Every several hundred years, peaks of charcoal influx were identified in the composite record, indicating that the peatlands repeatedly experienced dry conditions and wildfires. Major fire events were identified at ∼5.4, 4.7, 4.4, 3.7, 3.2, 2.7, 2.4, 2.2, 1.7, 1.1, 0.6, and 0.3 ka. Most of these coincided with the maxima of Borneo speleothem δ 18 O and occurred in the high solar activity periods following the solar minima. This suggests that the higher solar activity decreased rainfall, increasing dryness and wildfire frequency. This result challenges the hypothesis that high solar activity intensifies atmospheric convection in the WPWP area. Plain Language Summary: The charcoal influx in peat sequences shed light on the wildfire history in northern Borneo during the last 6, 000 years. The sequences indicate peaks of charcoal influx every several hundred years, suggesting that the peatlands repeatedly experienced dry conditions and wildfires. The major fire events occurred in the high solar activity period after the solar activity was at a minimum. This suggests that the climate was drier when the solar activity was stronger. This result challenges the idea that high solar activity induces more rainfall in the tropical Western Pacific area. Key Points: Charcoal influx in peats was evaluated to understand wildfire history and climate change in northern Borneo The charcoal record showed that fire events occurred every several hundred years in response to changes in solar activity Major fire events occurred in the high solar activity periods following the preceding solar minima